Decoding mixed messages in the developing cortex: Translational regulation of neural progenitor fate - Hoye, Mariah L. (Curr Opin Neurobiol, 2020)
Regulation of stem cell fate decisions is elemental to faithful development, homeostasis, and organismal fitness. Emerging data demonstrates pluripotent stem cells exhibit a vast transcriptional landscape, which is refined as cells differentiate. In the developing neocortex, transcriptional priming of neural progenitors, coupled with post-transcriptional control, is critical for defining cell fates of projection neurons. In particular, radial glial progenitors exhibit dynamic post-transcriptional regulation, including subcellular mRNA localization, RNA decay, and translation. These processes involve both cis- and trans-regulatory factors, many of which are implicated in neurodevelopmental disease. This review highlights emerging post-transcriptional mechanisms which govern cortical development, with a particular focus on translational control of neuronal fates including those relevant for disease.